The effects of Autonomous Sensory Meridian Response (ASMR) videos and ASMR group on state anxiety - Jairom, Presley (Penerbit Universiti Kebangsaan Malaysia, 2021)
The aim of this study is to investigate the effects of Autonomous Sensory Meridian Response (ASMR) videos and ASMR group on state anxiety, 212 Malaysians with no history of anxiety disorders were asked to watch both ASMR and non-ASMR videos. State anxiety levels were recorded immediately after watching each video. The participants were then characterised into either ASMR and non-ASMR group based on their responses on a grouping statement. Supplementary data analyses on participants’ subjective ASMR experiences and triggers were also explored. Results showed that non-ASMR group had higher state anxiety after watching the ASMR video, but no significant differences were found in the ASMR group. The findings contradict the hypotheses that ASMR group would have lower state anxiety after watching ASMR video. This suggests that a different form of atypical sensory phenomenon may be elicited in part of ASMR.